Kaidah Al-Muradhif Wal Musytarak Dalam Al-Qur’an - Fadhli, Fadhli; Agustiar, Agustiar (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
This article discusses the rules of al-Muradhif and al-Musytarak in the Qur'an, two profound linguistic concepts in Arabic analysis. The rule of al-Muradhif refers to the use of synonymous words to enrich the meaning of a text, while al-Musytarak deals with words that have the same root but are used in different contexts. This article outlines how these rules are reflected in Qur'anic verses, highlighting the importance of a deep understanding of the Arabic language's structure in understanding the Qur'an's message. This type of library research aims to explore the rules of al-Muradhif and al-Musytarak in the verses of the Qur'an. The data comes from various literature sources, including books, scientific papers, and articles relevant to the subject matter. This research focuses on exploring a deep understanding of the use of al-Muradhif and al-Musytarak rules in the context of the Arabic Qur'an. Through a literature approach, this study aims to contribute to a better understanding of linguistic aspects and meanings in Qur'anic verses that use these rules.